LEGAL ASPECTS OF CONDUCTING OF HANDWRITING RESEARCH - Veronika N. Shkabaro; Аlona V. Bila; Vladislav V. Voronin (Alfred Nobel University Journal of Law, 2022)
The article is devoted to the analysis of regulatory and legal aspects regarding the conduct and appointment of handwriting expertise in civil proceedings. It is noted that the legal nature of the handwriting examination presupposes the availability of special knowledge in the field of science, which allows with a very high percentage of accuracy to establish or disprove facts that are important in the consideration of a case and the resolution of a civil dispute. Handwriting expertise is important for both sides of the litigation. It was determined that the study of writing and handwriting has gone a long way in its development and the method of conducting handwriting research is constantly being improved. The concept of handwriting examination is characterized in the scientific work. The concept of “legal expert”, “civil litigation expert”, “judicial expert” was studied. Attention was drawn to the absence in the civil procedural legislation of Ukraine of a clear and detailed regulation of the concept, legal nature, procedure for collecting materials and direct forensic examination. The main legislative scientific-methodological recommendations on the preparation and appointment of handwriting examination have been analyzed. Emphasis was placed on the study of copies of handwritten records and signatures obtained by electronic means and electronic photographic means. The legal aspects of the assessment of the expert's decision based on the results of the court's handwriting examination have been studied. The role of handwriting research in the process of law enforcement is determined. Handwriting research is defined as one of the most effective means of proof. It was concluded that the expert's decision is a valid piece of evidence in the case, however, its content should be carefully checked and studied by the court, and the assessment should be carried out in combination with all the circumstances of the case. Problematic aspects of the researched area are formulated. Attention is focused on the lack of a proper mechanism of legal regulation in civil procedural legislation regarding a clear algorithm of court actions during the appointment of expertise, especially in the aspect of collecting material for expert research. Proposals have been made to improve the legislation regarding the procedure for collecting samples for handwriting examination and the direct participation of a judge in this process.